Bahasa Cina Bahasa Melayu: Kebolehterjemahan Budaya by Goh Sang Seong. Pulau Pinang: Penerbit Universiti Sains Malaysia, 2012, ix + 226 pp. - Jyh Wee Sew, (Kajian Malaysia, 2014)
Studies on the translation of English to Malay have received considerable attention from Southeast Asian scholars. Among others, Asmah (1979), Ainon (1991), Tham (1990) published lengthy discussions on the subject. In comparison, studies on the translation of Mandarin to Malay are less robust. This book provides a timely explanation on techniques of translating linguisticspecific terms and cultural-specific references in Chinese into Malay.